Philanthropy in health professions education research: determinants of success. Issue 5 (11th January 2017) - Paul, Robert; Hollenberg, Elisa; Hodges, Brian D
Abstract : Context: Fund‐raising is a new practice in medical education research. Objectives: This qualitative study explores a cross‐sectional analysis of philanthropy in medical education in Canada and Europe and identifies some common characteristics in the fund‐raising system, key roles and characteristics of research sites that have had success. Methods: Medical education research sites that had received donations greater than Can$100 000 were identified by searching publicly available sources. Interviews were conducted with 25 individuals from these and other sites, in four categories: medical education leaders ( n  = 9); philanthropy‐supported chairholders and researchers ( n  = 5); donors of over Can$100 000 ( n  = 7), and advancement professionals ( n  = 4). Interview transcripts were inductively coded to identify themes. Results: Five factors associated with success in accessing philanthropic sources were identified in the sample: support of the organisation's senior leadership; a charismatic champion who motivates donors; access to an advancement office or foundation; impetus to find funds beyond traditional operating budgets, and understanding of the conceptual and practical dimensions of fund‐raising. Three types of donor ( medical education insider, donor collective and general philanthropist ), four faculty roles ( trailblazers, rock stars, ' Who? Me?' people and future fund‐raisers ) and six stages in the fund‐raising cycle were also identified. Conclusions: Philanthropy is a source of funding with the potential to significantly advance education research. Yet competence in fund‐raising is not widely developed among medical education research leaders. Successful accessing of philanthropic sources of funding requires the ability to articulate the impact of philanthropy in medical education research in a way that will interest donors. This appears to be challenging for medical education leaders, who tend to frame their work in academic terms and have trouble competing against other fund‐raising domains. Medical education research institutes and centres will benefit from developing greater understanding of the conception and practices of fund‐raising.